Mimic makers : biomimicry inventors inspired by nature - Nordstrom, Kristen (Charlesbridge, 2021)
"In biomimicry, scientists imitate traits found in nature. An engineer shapes the nose of his bullet train like a kingfisher's beak. A scientist models her solar cell on the mighty leaf. Discover how eight inventors were inspired by animals and plants to create cutting-edge technology"--